Differentiating transudative and exudative pleural effusion by pleural fluid cholesterol - Ambresh, Ayyali; Mulimani, Mallanna S (International Journal of Clinical and Biomedical Research, 2019)
Background: Pleural effusion is one of the common condition encountered in day to day practise. Pleural effusions represent a very common diagnostic task to the physician. A correct diagnosis of the underlying disease is essential to rational management. Today there are a number of laboratory tests available to differentiate exudates and transudates which are considered cost effective to the patients, so this study was designed for the measurement of pleural fluid cholesterol to differentiate transudative and exudative pleural effusions (sensitivity-97.8%, specificity-100%) with the advantage that a contemporary blood sample is not required, thereby lowering cost of diagnostic procedure. Objectives: To study the diagnostic value of Pleural fluid Cholesterol in differentiating transudative and exudative pleural effusions. Methodology: This cross sectional descriptive study was conducted on patients of pleural effusion (n=60)age >18 years patients with definitive clinical diagnosis and evidenced by radiological diagnosis of pleural effusion were taken as inclusion criteria. Results: The results showed majority of the patients were males (63.3%) and females (36.7%). According to lights criteria 46 patients were exudates and 14 patients were transudates and according to Pleural fluid Cholesterol criteria 45 patients were exudates and 15 patients were transudates with sensitivity of 97.8% and specificity of 100% and accuracy of 98.3%. Conclusion: The pleural fluid cholesterol criteria were found to be the most efficient criteria. Since this parameter involves the measurement of only pleural fluid values of cholesterol, it has following advantages-Economically it reduces number of biochemical tests and Simpler as there is no need to take simultaneous blood sample at the time of thoracocentesis.